Penyuluhan dan Pelatihan Pembuatan The Celup Buah Mengkudu untuk Penggunaan Obat Tradisional di Ekowisata Sungkai Green Park - Yufri Aldi; Salman Umar; Dwisari Dillasamola; Wanda Azukhruf; Siti Jannah; Aditya Alianta (LPPM Universitas Andalas, 2025)
The use of plants as medicinal ingredients has significant potential for further development, particularly as public awareness of healthy living continues to grow. One of the plants long utilised as a traditional herbal remedy in Indonesia is the noni fruit (Morinda citrifolia L.). It is essential to enhance community awareness of the health benefits of noni fruit to ensure its proper processing, dosing, and optimal use duration. This community service activity was conducted at Ekowisata Sungkai Green Park, involving twenty-five female participants who are members of the Farmer Training and Self-Reliance Centre (P4S). The activity included an extension program featuring lectures, hands-on training, and evaluations. The training focused on the techniques for harvesting and preparing noni fruit powder in accordance with Good Traditional Medicine Manufacturing Practices. Additionally, question-and-answer sessions were held to enhance participants' understanding, and their knowledge was assessed through a structured questionnaire. The results showed high enthusiasm and active participation during both the practical and Q&A sessions on preparing noni fruit herbal tea bags. Participants demonstrated improved understanding of noni’s processing methods and its benefits as a natural immune-enhancing remedy. They also expressed interest in continuing similar programs in the future as part of a sustainable community-based initiative that could develop into small-scale herbal enterprises. Based on the evaluation, 92% of participants strongly agree, and 8% agree that these community services were beneficial. In conclusion, the program successfully increased community awareness and skills in utilising local medicinal plants for health and economic empowerment.